2022
DOI: 10.1038/s41598-022-18114-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice variant of Elp3/Kat9 regulates mitochondrial tRNA modification and function

Abstract: Post-translational modifications, such as lysine acetylation, regulate the activity of diverse proteins across many cellular compartments. Protein deacetylation in mitochondria is catalyzed by the enzymatic activity of the NAD+-dependent deacetylase sirtuin 3 (SIRT3), however it remains unclear whether corresponding mitochondrial acetyltransferases exist. We used a bioinformatics approach to search for mitochondrial proteins with an acetyltransferase catalytic domain, and identified a novel splice variant of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Interestingly, ELP3 has been found to localize to mitochondria in HeLa cells 34 and Toxoplasma gondii 35 . It was also recently reported that a novel splice variant of ELP3 is localized to the mitochondrial matrix, where it modifies mitochondrial tRNAs, and in so doing, protects the tRNAs from degradation 36 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, ELP3 has been found to localize to mitochondria in HeLa cells 34 and Toxoplasma gondii 35 . It was also recently reported that a novel splice variant of ELP3 is localized to the mitochondrial matrix, where it modifies mitochondrial tRNAs, and in so doing, protects the tRNAs from degradation 36 .…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, ELP3 has been found to localize to mitochondria in HeLa cells 34 and Toxoplasma gondii 35 . It was also recently reported that a novel splice variant of ELP3 is localized to the mitochondrial matrix, where it modifies mitochondrial tRNAs, and in so doing, protects the tRNAs from degradation 36 . If these mechanisms are also in play during brown adipogenesis, they will add a further dimension to how translational changes might be localized and effected.…”
Section: Discussionmentioning
confidence: 95%